2015
DOI: 10.1002/jhm.2370
|View full text |Cite
|
Sign up to set email alerts
|

Time to clinical stability among children hospitalized with pneumonia

Abstract: We evaluated the performance of Time to Clinical Stability (TCS), a longitudinal outcome measure using four physiologic parameters (temperature, heart rate, respiratory rate, and use of supplemental oxygen), among children enrolled in a prospective study of pneumonia hospitalizations. We calculated the time from admission to normalization for each of the four parameters individually and various combinations of these parameters (>2 parameters). We assessed for agreement between the combined TCS measures and bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 14 publications
9
10
1
Order By: Relevance
“…This study indicated that younger children recover sooner than older ones. This finding is in line with the study conducted on time to clinical stability among hospitalized children that reported higher hospital stay among children above five years than below [9]. The current finding is also supported by a study conducted in Italy on the prediction of delayed recovery from pediatric community-acquired pneumonia [19].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This study indicated that younger children recover sooner than older ones. This finding is in line with the study conducted on time to clinical stability among hospitalized children that reported higher hospital stay among children above five years than below [9]. The current finding is also supported by a study conducted in Italy on the prediction of delayed recovery from pediatric community-acquired pneumonia [19].…”
Section: Discussionsupporting
confidence: 92%
“…The finding of this study is almost similar to the study conducted in the rural health center of the Gambia which reported that the meantime of recovery was 4.5 days [16]. The finding of this study is higher than the study done at Vanderbilt (2.3days)and Nepal (2days) [9,17]. This variation might be due to case-mix, severity, and co-morbidity differences.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In this study, the only clinical finding that discriminated significantly between children with radiographically confirmed pneumonia and those with normal CXR was degree of fever. Higher body temperature has been associated with delay in achieving clinical stability, although pattern of fever was not associated with radiologic findings [26].…”
Section: Discussionmentioning
confidence: 99%
“…With the growing emphasis on decreasing hospital costs, concern exists that patients are being discharged from hospitals "quicker and sicker," 18,19 with shortening lengths of stay and higher patient instability at discharge. Clinical instability at discharge has been associated with adverse postdischarge outcomes in adults with pneumonia [20][21][22][23] ; however, studies evaluating discharge readiness have not examined the population of children with NI. Our findings of no difference in reutilization for children with NI discharged before return to respiratory baseline, which would be expected to approximate one or more clinical instabilities, contrast these concerns.…”
Section: Discussionmentioning
confidence: 99%